High-Speed Train-Track-Bridge Dynamic Interaction considering Wheel-Rail Contact Nonlinearity due to Wheel Hollow Wear - Chao Chang; Liang Ling; Zhaoling Han; Kaiyun Wang; Wanming Zhai (Shock and Vibration)
Wheel hollow wear is a common form of wheel-surface damage in high-speed trains, which is of great concern and a potential threat to the service performance and safety of the high-speed railway system. At the same time, rail corridors in high-speed railways are extensively straightened through the addition of bridges. However, only few studies paid attention to the influence of wheel-profile wear on the train-track-bridge dynamic interaction. This paper reports a study of the high-speed train-track-bridge dynamic interactions under new and hollow worn wheel profiles. A nonlinear rigid-flexible coupled model of a Chinese high-speed train travelling on nonballasted tracks supported by a long-span continuous girder bridge is formulated. This modelling is based on the train-track-bridge interaction theory, the wheel-rail nonelliptical multipoint contact theory, and the modified Craig–Bampton modal synthesis method. The effects of wheel-rail nonlinearity caused by the wheel hollow wear are fully considered. The proposed model is applied to predict the vertical and lateral dynamic responses of the high-speed train-track-bridge system under new and worn wheel profiles, in which a high-speed train passing through a long-span continuous girder bridge at a speed of 350 km/h is considered. The numerical results show that the wheel hollow wear changes the geometric parameters of the wheel-rail contact and then deteriorates the train-track-bridge interactions. The worn wheels can increase the vibration response of the high-speed railway bridges.